Patient Awareness and Attitudes Toward Intravenous Contrast Materials (IVCMs) Risks at King Abdulaziz Medical City (KAMC), Riyadh, Saudi Arabia - Oinam Gokulchandra Singh,; Nawaf Alshahrani,; Honnegowda Thittamaranahalli Muguregowda,; Faisal M Abu Aljadaiyl,; Faisal Alsaab,; Ahmed Bedaiwi,; Muath Alqahtani,; Fayaz Ul Haq,; Alaa Alangary,; Abdullah M Al Shahrani,; Turki Qaryan Alanazi,; Sultan Saad Albugami,; et al. (Utilitas Mathematica, 2025)
Aim of the Study This research seeks to comprehensively explore the levels of knowledge and attitude among patients at King Abdul-Aziz Medical City in Riyadh, Saudi Arabia, regarding intravenous contrast materials (IVCMs) and their associated risks. Specific Objectives To assess the knowledge and attitude levels of patients concerning intravenous contrast media, including an exploration of risk factors and side effects. Materials & Methods A cross-sectional study was conducted using a self-administered questionnaire in King Abdul- Aziz Medical City, Riyadh, Saudi Arabia. The 180 participants were exposed to 14 items to assess their knowledge and attitudes towards their risk and about the IVCMs and their role in the diagnosis of some diseases. Eligible patients who had undergone contrast radiological study in Fluoroscopy and CT imaging modality. The mean percentage scores were correlated with the specialty, level of age, gender, education, use of radiation protective tools and frequency of contrast study requisition. Results Out of 180 participants, 59.4% were males, and 68.3% underwent angiography as the primary radiological exam. Participants expressed agreement on the harmful effects of IVCM (47.2%) and the necessity of removing metallic objects during radiological procedures (82.2%). The mean knowledge score was 1.14 with a standard deviation of 0.85. No statistical significance was found between knowledge scores and demographic variables (p value < 0.05). Conclusions: Overall, the findings underscore the importance of improving communication and education efforts to support informed decision-making and enhance patient safety in radiological practices